(untitled) (Journal of Computational Mathematics, 2018)
In this paper, a class of DBDF methods with the derivative medifying term is presented. The methods is ^k_j=0a_jy_n+j=hf_n+k+ah^2f'_n+k which is of k-step and order k+1. The numerical stability of the new method is much better than both Gear's methods and Enright's methods.